Paraneoplastic Polymyositis in a Patient of Myelofibrosis (Journal of Armed Forces Medical College, Bangladesh, 2020)
Polymyositis is a rare rheumatologic disorder. Exact cause is unknown but autoimmunity, genetic and environmental factors like infection and drugs may be responsible. It may be a primary autoimmune disease, associated with other autoimmune diseases or underlying malignancy. There is two-way relationship between polymyositis and malignancy. Patients with polymyositis and dermatomyositis has increased chance of various malignancies. On the other hand polymyositis and dermatomyositis may be a paraneoplastic manifestation of some malignancies like carcinoma lung, ovary, breast, pancreas, colon, lymphoma, MDS and myeloproliferative disorders. We have diagnosed a case of polymyositis in a patient of Myelofibrosis (MF). The patient presented with inflammatory myopathy affecting proximal muscles of the limbs, neck muscles, laryngeal and pharyngeal muscles. Muscle enzymes were markedly elevated, EMG and MRI were in favour of inflammatory myopathy. Muscle biopsy showed inflammatory infiltrates in muscles mostly by T- cells with myonecrosis, degeneration and regeneration without vasculopathy and perivascular change. Primary polymyositis and other autoimmune diseases were excluded by absence of relevant autoantibodies. So he was diagnosed as a case of paraneoplastic polymyositis.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 116-118